Implementation of ZVS interleaved booster converter in Electric vehicles with reduced THD - Abubaker Emheisen; Mustafa Emheisen (African Journal of Advanced Pure and Applied Sciences, 2025)
With the increase in global infrastructure, electric vehicles (EVs) are the replacement for many conventional transportation. In recent years, there has been significant development in EV technology to increase efficiency and reduce the THD of the machine. This paper proposes a new converter topology ZVS interleaved booster converter, for traction purposes when connected to the smart grid. The analysis and performance with complete modes of operation is been discussed with a graphical representation of outputs of the DC machine. The modeling and analysis are done using MATLAB Simulink.